Reimagining Education: The International Science and Evidence Based Education Assessment 2022
DOI: 10.56383/xbxz7711
|View full text |Cite
|
Sign up to set email alerts
|

Education for flourishing and flourishing in education

Abstract: T his chapter aims to elucidate theoretical meanings of ourishing and education, and the relation between them. Throughout history a variety of ideas about the nature and purpose of these activities has been developed. This chapter considers the purpose and aims of education. It will explicate what viewing this purpose or ultimate aim may mean in terms of human ourishing and how ideas about human ourishing in uence thinking about the practice of education and vice versa, given they are perceived as being in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Our study is one of few providing insight into opportunities to improve FCC for families from historically marginalized communities, highlighting the need to understand each family's context and provide supports that meets people's needs and accounts for their challenges (Browne et al, 2012; Mugerauer, 2021; Sheldrick et al, 2021). One important step is eliciting parents' multidimensional conceptualizations of health; we found that parents' definitions broadly reflect flourishing, a popular concept focusing on social and cultural factors that are central to conceptualizations of well‐being (de Ruyter et al, 2020). The diversity of the conceptualizations we found parallels the findings of studies among other marginalized groups (Bircher, 2005; Boddington & Raisanen, 2009; Dodgson & Struthers, 2005; Gessert et al, 2015; Leonardi, 2018; Song & Kong, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Our study is one of few providing insight into opportunities to improve FCC for families from historically marginalized communities, highlighting the need to understand each family's context and provide supports that meets people's needs and accounts for their challenges (Browne et al, 2012; Mugerauer, 2021; Sheldrick et al, 2021). One important step is eliciting parents' multidimensional conceptualizations of health; we found that parents' definitions broadly reflect flourishing, a popular concept focusing on social and cultural factors that are central to conceptualizations of well‐being (de Ruyter et al, 2020). The diversity of the conceptualizations we found parallels the findings of studies among other marginalized groups (Bircher, 2005; Boddington & Raisanen, 2009; Dodgson & Struthers, 2005; Gessert et al, 2015; Leonardi, 2018; Song & Kong, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Identity development during late adolescence is nurtured within respectful and autonomous learning environments that offer emotional support for students to express and reflect on their experiences (Lapsley, 2010;Magolda & Taylor, 2015). This aligns with the growing recognition of the importance of fostering open-minded moral inquiry in high schools through a dialogical approach, which supports the identity formation of high school students The topic of moral education at school is a current subject of debate in recent scientific literature (e.g., OECD, 2021;Singh, 2019;Stevenson, 2022;De Ruyter et al, 2022). Similarly, in Latvia there are controversial and overlapping interpretations of what constitutes moral education.…”
Section: Introductionmentioning
confidence: 82%
“…Many other definitions have been proposed (Darwall, 1999;de Ruyter et al, 2022;Foot, 2001;Kraut, 1989Kraut, , 2007Kristjánsson, 2020;Paul et al, 1999;Vitterosø, 2016;Waterman, 2013), including by some of us, but we accept this definition as compatible with common usage and as incorporating defining aspects of flourishing common to a wide range of philosophical and psychological accounts of it. 2 Having explained how we will use the terms 'well-being', 'thriving', 'happiness', 'happy', and 'flourishing' throughout this article, we also acknowledge that our choices are to some extent arbitrary.…”
Section: Conceptual Preliminariesmentioning
confidence: 89%